Low-field NMR: A new alternative to determine the aromatic content of petroleum distillates. (1st March 2019) - Montes, Luciana F.; Oliveira, Emanuele C.S.; Neto, Álvaro C.; Menezes, Sônia M.C.; Castro, Eustáquio R.V.; Barbosa, Lúcio L.
Highlights: The transversal relaxation time was used to predict aromatic content of the distillates. Rapid analysis and non-destructive showed that low field NMR can be used for analysis of routine in the oilfield. Hydrogen and carbon aromatic content, i.e, fa values were determined simultaneously with only one measure by low field NMR. Abstract: Petroleum and distillates contain different concentrations of aromatic hydrocarbons. These compounds are important downstream as process indicators for product formulation. They can reduce the calorific value of some distillates, poison catalysts, be resistant to certain processes, and can provoke environmental impacts. The quantification of these compounds expressed by aromaticity factor ( fa ) is usually determined using 13 C high-resolution NMR spectroscopy following the procedure of the ASTMD5292 standard test. However, this technique presents some disadvantages, such as long time of analysis, high cost and the use of solvents for sample preparation. In this study we proposed the use of low-field NMR (LF-NMR) at 2.2 MHz for detecting the 1 H nucleus as an interesting, quicker and cheaper alternative to estimate the fa value of 42 distillates produced from atmospheric distillation (ASTMD2892 method) of four oils with °API between 17.9 (heavy) and 34.9 (light). The results showed the great potential of LF-NMR to quantify the aromaticity in light, medium and heavy distillates with aromatic carbon (Car ) contents between 0.4 and 13.9 wt%. Furthermore, it was possible predict fa values, either hydrogen or carbon, based only on the transverse relaxation time (T2 ) obtained from the NMR experiments in time domain.